PERBEDAAN KEEFEKTIFAN MENYIKAT GIGI TEKNIK ROLL (MODIFIKASI STILLMAN) DENGAN TEKNIK FONES (SIRKULER) TERHADAP PEMBENTUKAN PLAK BARU Penelitian pada Sekolah Dasar Negeri Percobaan 2 Yogyakarta - Fahma Fauziah Fachru (2013)

(untitled)
Plaque is soft attached deposit on the tooth surface comprising of microorganism that could multiply in a cellular matrix. The cause of the caries and periodontal disease mostly occurs due to plaque that couldn't remove completely. The plaque formation has been formed through three stages, the first stage is characterized by acquired pelicle which comprised of mucoprotein and salivary glycoprotein involving aerobic bacteria. Those form extracellular polysaccharides called the newly formed plaque